A mechanism for FtsZ-independent proliferation in Streptomyces. Issue 1 (December 2017) - Santos-Beneit, Fernando; Roberts, David; Cantlay, Stuart; McCormick, Joseph; Errington, Jeff
Abstract The central player in bacterial cell division, FtsZ, is essential in almost all organisms in which it has been tested, with the most notable exception beingStreptomyces . Streptomycetes differ from many bacteria in growing from the cell tip and undergoing branching, similar to filamentous fungi. Here we show that limited cell damage, either mechanical or enzymatic, leads to near complete destruction of mycelial microcolonies of aStreptomyces venezuelae ftsZ mutant. This result is consistent with a lack offtsZ -dependent cross-walls and may be inconsistent with a recently proposed role for membrane structures in the proliferation offtsZ mutants in otherStreptomyces species. Rare surviving fragments of mycelium, usually around branches, appear to be the preferred sites of resealing. Restoration of growth in hyphal fragments of both wild-type andftsZ mutant hyphae can occur at multiple sites, via branch-like outgrowths containing DivIVA protein at their tips. Thus, our results highlight branching as a means of FtsZ-independent cell proliferation. Protein FtsZ plays key roles in cell division and is essential in most bacterial species; exceptions include streptomycetes, which grow from the cell tip and form branched hyphae. Here, Santos-Beneitet al . show that branching allows FtsZ-independent proliferation inStreptomyces venezuelae .